If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( y )
y-9 = 0
y-9 = 0
y-9 = 0
y-9 = 0 // + 9
y = 9
y in (-oo:9) U (9:+oo)
(4*y)/(y-9)+(5/2)*y = -9/2 // + -9/2
(4*y)/(y-9)+(5/2)*y-(-9/2) = 0
(4*y)/(y-9)+(5/2)*y+9/2 = 0
(4*y)/(y-9)+(5*y)/2+9/2 = 0
(2*4*y)/(2*(y-9))+(5*y*(y-9))/(2*(y-9))+(9*(y-9))/(2*(y-9)) = 0
5*y*(y-9)+9*(y-9)+2*4*y = 0
5*y^2-37*y+9*y-81 = 0
5*y^2-28*y-81 = 0
5*y^2-28*y-81 = 0
5*y^2-28*y-81 = 0
DELTA = (-28)^2-(-81*4*5)
DELTA = 2404
DELTA > 0
y = (2404^(1/2)+28)/(2*5) or y = (28-2404^(1/2))/(2*5)
y = (2*601^(1/2)+28)/10 or y = (28-2*601^(1/2))/10
(y-((28-2*601^(1/2))/10))*(y-((2*601^(1/2)+28)/10)) = 0
((y-((28-2*601^(1/2))/10))*(y-((2*601^(1/2)+28)/10)))/(2*(y-9)) = 0
((y-((28-2*601^(1/2))/10))*(y-((2*601^(1/2)+28)/10)))/(2*(y-9)) = 0 // * 2*(y-9)
(y-((28-2*601^(1/2))/10))*(y-((2*601^(1/2)+28)/10)) = 0
( y-((2*601^(1/2)+28)/10) )
y-((2*601^(1/2)+28)/10) = 0 // + (2*601^(1/2)+28)/10
y = (2*601^(1/2)+28)/10
( y-((28-2*601^(1/2))/10) )
y-((28-2*601^(1/2))/10) = 0 // + (28-2*601^(1/2))/10
y = (28-2*601^(1/2))/10
y in { (2*601^(1/2)+28)/10, (28-2*601^(1/2))/10 }
| -5x=2x-4 | | (-5x)=2x-4 | | -4(2b+1)+(9b-5)=0 | | 19j+16=8 | | (-5)*(x)=2x-4 | | 5r^2+34r+45=0 | | 5.9q-3.8-5.5q=-0.6q-5.4 | | 2*x=x^2-4*x | | 7.3x-2x=-4x+4 | | 2(x)=x*x-4x | | 3x-5+2x+8=x+4+3x-12 | | 4=2x-4 | | 7=6y | | (-5)=a/18 | | 9.5*+12.5=50.5 | | n-8=(-10) | | 5x+3=4x-8 | | n+1*n-6=0 | | n+1*n-6=9 | | n-6=0 | | 4/c-5/7 | | (-7)+m=8 | | s-18=-35 | | (-17)=x-15 | | 30=-5U | | a^2-9-52=0 | | 0.25h+9=0,75h-7 | | (-16)+x=(-15) | | 7l+3w=h | | (-16)+x=(-5) | | (-143)=(-11x) | | 120+7l+3w=h |